The occurrence and spatial-temporal distribution of tetrabromobisphenol A in the coastal intertidal zone of Qingdao in China, with a focus on toxicity assessment by biological monitoring. (October 2017) - Gong, Wen-jing; Zhu, Li-yan; Jiang, Tian-tian; Han, Cui
Abstract: Tetrabromobisphenol A (TBBPA) is a widely used flame retardant that has increasingly been found as contaminant in aquatic environments. The main goal of this study was to evaluate the pollution level of TBBPA at six locations around Qingdao and assess its biotoxicity through a two-generation toxicity study looking at a copepod species. In the chemical monitoring, the concentration of TBBPA in seawater samples ranged from nd to 1.8 μg/L. Next, the biological indicator monitoring used 1.8 μg/L as the middle exposure concentration to perform quantitative evaluations of the influence of TBBPA on the demographic traits of Pseudodiaptomus inopinus . The results showed that copepods became more sensitive to TBBPA exposure even in environmental concentration (1.8 μg/L) as the generations developed. The detrimental effects of TBBPA further increased naupliar mortality and impaired copepodite development to adulthood. This study demonstrated that the water pollution condition of TBBPA was measured at all 6 sampling locations of Qingdao. Therefore, the present results call for a decreased discharge of TBBPA into the marine environment to avoid impairing copepod reproduction and development. Highlights: We evaluated the pollution level of TBBPA in the coastal intertidal zone of Qingdao by the chemical monitoring. We demonstrated that the water pollution condition of TBBPA was generally present in sampling places of Qingdao. We assessed the biotoxicity of TBBPA through a two-generation toxicity study looking at the copepod species. The detrimental effects of TBBPA could increase naupliar mortality and impair copepodite development to adulthood.